2022
DOI: 10.1186/s42155-021-00281-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of emergency transarterial embolization for mesenteric bleeding

Abstract: Background Patients with spontaneous or traumatic active mesenteric bleeding cannot be treated endoscopically. Transarterial embolization can serve as a potential alternative to emergency surgery. Literature on transarterial embolization for mesenteric bleeding remains very scarce. The objective of this study was to evaluate the safety and efficacy of transarterial embolization for mesenteric bleeding. We reviewed all consecutive patients admitted for mesenteric bleeding to the interventional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…There have been reports on the use of NBCA as an intravascular embolic material for treating various diseases, such as embolization of aneurysms to prevent rupture 9) , hemostasis for severe bleeding [10][11][12][13] , embolization to control blood loss before surgical removal of hypervascular tumors 14,15) , embolization for vascular malformation [16][17][18] , arterial redistribution before transarterial treatment 19) , and embolization for endoleak after aortic stent placement 20,21) . The use of NBCA embolization to treat cerebrovascular disease 16,18) and varicose veins 22) has been reported by several prospective studies; however, only a few prospective studies have reported on its use to treat other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports on the use of NBCA as an intravascular embolic material for treating various diseases, such as embolization of aneurysms to prevent rupture 9) , hemostasis for severe bleeding [10][11][12][13] , embolization to control blood loss before surgical removal of hypervascular tumors 14,15) , embolization for vascular malformation [16][17][18] , arterial redistribution before transarterial treatment 19) , and embolization for endoleak after aortic stent placement 20,21) . The use of NBCA embolization to treat cerebrovascular disease 16,18) and varicose veins 22) has been reported by several prospective studies; however, only a few prospective studies have reported on its use to treat other diseases.…”
Section: Discussionmentioning
confidence: 99%